2018
DOI: 10.1007/s13205-018-1476-8
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and conservation analyses of MFS transporters

Abstract: Major facilitator superfamily is one of the largest superfamily of secondary transporters present across the kingdom of life. Considering the physiological and clinical importance of MFS proteins, we attempted to explore the phylogenetic and structural aspects of the superfamily. To achieve the objectives, we performed global sequence-based analyses of MFS proteins encompassing multiple taxa. Notably, phylogenetic analysis of MFS proteins resulted in the clustering of MFS proteins based on their function, rath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The number of transmembrane domains was obtained from Uniprot and literature cited in the respective sections. This table was assembled using information from [36] and [559]. For more specific structural information for these protein families, the reader is referred to Bai et al [36].…”
Section: Slc Superfamilymentioning
confidence: 99%
“…The number of transmembrane domains was obtained from Uniprot and literature cited in the respective sections. This table was assembled using information from [36] and [559]. For more specific structural information for these protein families, the reader is referred to Bai et al [36].…”
Section: Slc Superfamilymentioning
confidence: 99%
“…Many transporter proteins are highly conserved and while the exact distribution and localization might not be the same across species, the function is more often conserved. Phylogenetic analysis of transporters belonging to the MFS result in function based clustering rather than lineage based (Vishwakarma et al, 2018). GLUT1 is also responsible for glucose uptake in Drosophila melanogaster, however, not across the BBB as in humans, but rather into neurons in the brain (Volkenhoff et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We found that protein families, which have previously attracted attention, have dynamic evolutionary histories reflecting their adaptive potential towards new ecological challenges. Among others, ABC and MFS transporters, which enable resistance against multiple environmental threats [152,153], are proteins involved in fungal cell wall biosynthesis such as chitin synthases (GT2) essential for interactions with other organisms and fungal defence [47]. Nutritional mode has a profound impact on the evolution of fungal genomes and the majority of differentially represented protein families in fungal proteomes are indeed associated with the digestion of nutrients (e.g., chitinases GH19 in fungi living with insects and loss of acetyl-xylan esterases CE2 and CE6 in endomycorrhizal Glomeromycota).…”
Section: Discussionmentioning
confidence: 99%